Microbial metabolites: novel therapeutic tools for boosting cancer therapies. Issue 11 (November 2021) - Luu, Maik; Visekruna, Alexander
Abstract : The microbiome is a hidden treasure trove comprising various microorganisms that produce a wide range of bioactive molecules. Recent studies provide evidence for the potential impact of microbiota on cancer therapies. Here, we summarize how the molecular interaction of two groups of microbial metabolites with T cells improves immunotherapy for cancer.